GEOCHEMICAL OF RARE EARTH ELEMENT AND GRAIN SIZE DISTRIBUTION OF HEAVY MINERALS ASSOCIATED WITH TIN DEPOSITS PLACER-TYPE, BANGKA ISLAND - Sulastri, Asti
Geographically, Indonesia is included in the South East Asian Tin Belt which extends from Myanmar to Indonesia. The factors that control the formation of tin deposits placer-type are the source rock (granite type S), weathering, erosion, transportation and sedimentation, as well as the presence of basins or valleys where weathering material is deposited. Ancient and modern sedimentary deposits have significant sourc Geographically, Indonesia is included in the South East Asian Tin Belt which extends from Myanmar to Indonesia. The factors that control the formation of placer tin deposits are the existence of source rocks (granite type S), weathering, erosion, transportation and sedimentation, as well as the presence of basins or valleys where weathering material is deposited. Ancient and modern sedimentary deposits have significant sources of rare earth elements. Rare earth element bearing minerals are monazite and xenotime which are minerals with high density or present as heavy minerals. The placer tin product is the result of the breakdown of the original rock which contains the associated bearing mineral of rare earth elements which are heavy minerals. The purpose of this study was to determine the characteristics of heavy mineral grains and the distribution of rare earth elements in several morphological peak domains, such as Menumbing, Jebus and Pemali, Mangkol, Bebulu, and Toboali on Bangka Island. The data used are 62 data 36 are secondary data and 26 data are derived from data collection in the field. The methods used are grain counting, grain texture analysis such as grain histogram and grain morphology, and ICP-MS analysis. The results of this study were the ratio of heavy minerals in alluvial and tailings samples in Bangka Island ranged from 5-35%. Cassiterite, monazite and zircon minerals were concentrated in the coarse fraction, while xenotime was concentrated in the fine fraction. Starting from upstream to downstream a heavy mineral grain is more mature in terms of grain histogram and grain morphology. The alluvial enrichment of rare earth elements is found in the Toboali area around 1.643 ppm and tailings samples are in the Menumbing area with a concentration of 11.208 ppm.